A critical review on livestock manure biorefinery technologies: Sustainability, challenges, and future perspectives. (January 2021) - Khoshnevisan, Benyamin; Duan, Na; Tsapekos, Panagiotis; Awasthi, Mukesh Kumar; Liu, Zhidan; Mohammadi, Ali; Angelidaki, Irini; Tsang, Daniel CW.; Zhang, Zengqiang; Pan, Junting; Ma, Lin; Aghbashlo, Mortaza; et al.
Abstract: An ever increasing demand for animal protein products has posed serious challenges for managing the increasing quantities of livestock manure. The choice of treatment technologies is still a complicated task and considerable debates over this issue still continue. To build a clearer picture of manure treatment framework, this study was conducted to review the most frequently employed manure management technologies from their state of the art, challenges, sustainability, environmental regulations and incentives, and improvement strategies perspectives. The results showed that most treatment technologies have focused on the solid fraction of manure while the liquid fraction still remains a potential environmental threat. Compared to other waste to energy solutions, anaerobic digestion is the most mature technology to upgrade manure's organic matter into renewable energy, however the problems associated with high investment costs, operating parameters, manure collection, and digestate management have hindered its developments in rural areas in developing countries. Bio-oil production through hydrothermal liquification is also a promising solution, as it can directly convert the wet manure into biofuel. However, lipid-poor nature of manure, operational difficulties, and the need for downstream process to remove nitrogenous compounds from the final product necessitate further research. Livestock manure management (both solid and liquid fractions) under biorefinery approach seems an inevitable solution for future sustainable development to meet circular bioeconomy requirements. Much research is still required to establish a systematic framework based on regional requirements to develop an integrated manure nutrient recycling and manure management planning with minimum environmental risks and maximum profit. Highlights: Challenge and future perspective of manure management technologies are discussed. Manure management technologies were compared from environmental viewpoints. Role of different groups involve in manure management circular loop was established. Product is the vital link of the policy, technology and environment assessment.